Odpowiedź :
[tex]zad.1\\\\-x^{2} +3x-x^{2} +2 >0\\\\-2x^{2} +3x+2>0\\\\a=-2, ~~b=3,~~c=2\\\\\Delta=b^{2} -4ac\\\\\Delta=3^{2} -4\cdot (-2)\cdot 2\\\\\Delta=9+16=25,~~\sqrt{\Delta} =5\\\\x_{1}=\dfrac{-b-\sqrt{\Delta} }{2a} ~~\land~~x_{2}=\dfrac{-b+\sqrt{\Delta} }{2a} \\\\x_{1} =\dfrac{-3-5}{-4} ~~\land~~x_{2} =\dfrac{-3+5}{-4}\\\\x_{1}=2~~\land~~ x_{2} =-\frac{1}{2} \\\\ramiona ~~paraboli~~skierowane~~sa~~w ~~dol~~a=-2\\\\x\in(-\frac{1}{2} ; 2)\\[/tex]
[tex]zad.2\\\\-(x-3)((x-1)\geq 0~~\mid\cdot (-1)\\\\(x-3)((x-1)\leq 0\\\\x-3=0~~\lor ~~x-1=0\\\\x=3~~\lor ~~x=1\\\\a=1 ~~\Rightarrow ramiona~~paraboli~~skierowane~~do ~~gory\\\\x\in <1; 3>[/tex]
[tex]zad.3\\\\(-x-3)(x-1)\geq 0\\\\-x-3=0~~\lor~~x-1=0\\\\x=- 3~~\lor~~x=1\\\\a=- 1 ~~\Rightarrow ramiona~~paraboli~~skierowane~~w~~dol\\\\x\in<- 3 ; 1 >[/tex]